2019
DOI: 10.1002/we.2422
|View full text |Cite
|
Sign up to set email alerts
|

A prediction approach using ensemble empirical mode decomposition‐permutation entropy and regularized extreme learning machine for short‐term wind speed

Abstract: Accurate prediction of short-term wind speed is of great significance to the operation and maintenance of wind farms, the optimal scheduling of turbines, and the safe and stable operation of power grids. A prediction approach for short-term wind speed using ensemble empirical mode decomposition-permutation entropy and regularized extreme learning machine is proposed. Firstly, wind speed time series is decomposed into several components with different frequency by ensemble empirical mode decomposition, which ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 97 publications
(61 citation statements)
references
References 51 publications
0
61
0
Order By: Relevance
“…In order to compare the goodness of fit of the least square method, the rational number approximation method without destroying the data distribution law is selected. There are several performance indicators added, such as root square derror (RMSE) [50], sum of squares due to error (SSE), R 2 and Adjusted R 2 [51]. Figure 10, Figure 11 and Figure 12 are the renderings after the two methods are fitted.…”
Section: B Melting Law Of Characteristic Parametersmentioning
confidence: 99%
“…In order to compare the goodness of fit of the least square method, the rational number approximation method without destroying the data distribution law is selected. There are several performance indicators added, such as root square derror (RMSE) [50], sum of squares due to error (SSE), R 2 and Adjusted R 2 [51]. Figure 10, Figure 11 and Figure 12 are the renderings after the two methods are fitted.…”
Section: B Melting Law Of Characteristic Parametersmentioning
confidence: 99%
“…The reason why Reliability is introduced is to evaluate the Reliability of confidence intervals. The definition of these performance indicators are as the follows 60 : RMSE=1Ni=1Ntitruet¯i2, MAE=1Ni=1Ntitfalse¯i, MAPE=1Ni=1Ntitfalse¯iti×100%, SSE=i=1Ntitruet¯i2, TIC=1N()titfalse¯i21Ni=1Nti2+1Ni=1Ntruet¯i2, IA=1i=1Ntitruet¯i2…”
Section: Case Studiesmentioning
confidence: 99%
“…The feature vector of the FFT processed sequence was later used as the training sequence. In accordance with successful experience [55] and multiple attempts, in this paper, 60% of the data was used for training, 20% of data was used for testing, and 20% of data was used for validation. It was confirmed that the above proportion has the best training performance for the subsequent processes.…”
Section: Preparation Of Datamentioning
confidence: 99%